PENGARUH TINGKAT PERTUMBUHAN PENJUALAN, PERPUTARAN PIUTANG, DAN PERPUTARAN KAS TERHADAP TINGKAT LIKUIDITAS PERUSAHAAN (STUDI KASUS PERUSAHAAN PERHOTELAN YANG TERDAFTAR DI BEI PERIODE 2017-2022) - Nurzammi Annisak; Khadijah Nurani (CV. ADIBA AISHA AMIRA, 2024)
This research aims to find out and analyze how much influence the level of sales growth, receivables turnover and cash turnover has on the level of company liquidity in hotel companies listed on the IDX for the 2017-2022 period. This type of research is quantitative research, the type of data is secondary data which is accessed via the official website of the Indonesia Stock Exchange (www.idx.co.id) and the websites of each company. The sampling technique used in this research was the purposive sampling method with a total sample of 14 companies. Data analysis techniques use descriptive statistical tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination tests. The results of this research partially show that the Sales Growth Rate variable has a positive and significant influence on the Liquidity Level as evidenced by the results of the tcount > ttable test (3.029 > 2.026). Receivables Turnover has a negative and significant effect on Liquidity Levels as proven by the results of the tcount < ttable test (-7.633 < 2.056). Cash Turnover has a positive and significant effect on Liquidity Levels as proven by the results of the tcount > table test (3.819 > 2.056). Sales Growth Rate, Receivables Turnover, and Cash Turnover together have a positive and significant effect on the Liquidity Level as proven by the results of the hypothesis test which shows a significance value of 0.000 < 0.05 and a comparison of the value of fcount > ftable (24.108 > 2.980) meaning Ho rejected